2013
DOI: 10.1007/s00044-013-0829-4
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin inhibitory activity of some polyphenolic compounds

Abstract: Thrombin, also known as an active plasma coagulation factor II, belongs to the family of serine proteases and plays a crucial role in blood coagulation process. The process of thrombin generation is the central event of the hemostatic process and regulates blood coagulant activity. For this reason, thrombin inhibition is key to successful novel antithrombotic pharmacotherapy. The aim of our present study was to examine the effects of the well-known polyphenolic compounds on the activity of thrombin, by charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 40 publications
3
42
0
Order By: Relevance
“…Although some phenolic compounds may influence the thrombin response (Bijak et al, 2014), it is still very premature to infer effects of these compounds derived from seaweeds on the TG system because no studies have also been done. Furthermore, the use of the papain method as mentioned above results in purity and enhanced yield of biologically active SPs for biotechnology (Athukorala et al, 2006;Mourão, 2015;Araújo et al, 2016) displaying in vitro TG inhibition (Glauser et al, 2009;Rodrigues et al, 2016b;Rodrigues et al, 2017a;Rodrigues et al, 2017b;Rodrigues et al, 2017c).…”
Section: Electrophoretic Analyses Reveal Physical-chemical Homogeneitmentioning
confidence: 99%
“…Although some phenolic compounds may influence the thrombin response (Bijak et al, 2014), it is still very premature to infer effects of these compounds derived from seaweeds on the TG system because no studies have also been done. Furthermore, the use of the papain method as mentioned above results in purity and enhanced yield of biologically active SPs for biotechnology (Athukorala et al, 2006;Mourão, 2015;Araújo et al, 2016) displaying in vitro TG inhibition (Glauser et al, 2009;Rodrigues et al, 2016b;Rodrigues et al, 2017a;Rodrigues et al, 2017b;Rodrigues et al, 2017c).…”
Section: Electrophoretic Analyses Reveal Physical-chemical Homogeneitmentioning
confidence: 99%
“…Silybin is also studied as a potential anticancer and chemo-preventive agent [ 13 ]. Research performed last year demonstrates that silybin is able to inhibit serine proteases involved in the blood coagulation process [ 14 , 15 ], as well as reduce blood platelets’ response to physiological agonists [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thrombin is composed of two polypeptide chains of 36 (A chain) and 259 (B chain) residues that are covalently linked through a disulfide bond, and the B chain carries the functional epitopes of the enzyme [ 3 ]. As same as all chymotrypsin-like serine proteases, thrombin has a conserved active centre located inside the molecule and contains amino acid residues of HIS57, ASP102, and SER195, which are called the catalytic triad [ 4 ]. Except for its active centre, thrombin possesses two exosites (1 and 2), positively charged domains located at opposite poles of the enzyme, among them, exosite 1 is utilized to dock on the substrates such as fibrinogen, and exosite 2 serves as the heparin-binding domain [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [ 12 ] evaluated a series of natural flavonoids as potential thrombin inhibitors by optimized method of thrombin time and found that myricetin and quercetin were the best thrombin inhibitors. Bijak et al [ 4 ] showed that cyanidin, quercetin, and silybin changed thrombin proteolytic activity, while cyanidin and quercetin caused a strong response in the interaction with immobilized thrombin by BIAcore analyses. Thus, their results suggested that polyphenolic compounds might be potential structural bases and source to find and project nature-based, safe, orally bioavailable direct thrombin inhibitors.…”
Section: Introductionmentioning
confidence: 99%